The Analysis of Rubric Feasibility Using Video Snippets of Learning Process - Hamdu, Ghullam; Suryani, Iis (Universitas Pendidikan Indonesia, 2019)
Multiple interpretations can cause a decrease in the quality of rubrics. This research aims at developing an appropriate rubrics description for the measurement of students' scientific attitudes. The process of developing the rubrics was done by using the video snippets of learning process. A total of 23 observers whose final year students were involved in analyzing the video snippets of learning process. They assessed eight indicators of the scientific attitude of ten students through the video snippets. The feasibility of the rubric is considered based on the responses given by 85% of the observers who have the similar answer to the scientific attitude of students in the video snippets of learning process. The description test of the rubrics was analyzed descriptively, which then obtained two rubrics that obtained answer differences less than 85% of the observers. Therefore, this research focuses on investigating the two rubrics. This research implies that there needs to be a clear description of the rubrics in relations to the time of observation of the number of students and behaviors.